FLAVONOID FROM METHANOLIC EXTRACT OF LIMONIASTRUM FEEI (GIRARD) BATT (PLUMBAGINACEAE) - L, ZIANE; Lazouni HA,; Moussaoui A,; Hamidi N,; Djellouli M,; Belabbes A, (Asian Journal of Pharmaceutical and Clinical Research, 2015)
According to the biological screening results of several extracts from three parts (leaves, stems and twigs) of Limoniastrum feei (plumbagenaceae) against fungi (Candida albican, sacharomyce), and bacteria (Escherechia coli, Staphylococcus aureus, Pseudomonas aeruginosa, Klebseilla entercoccus) realized by disc diffusion method, we interested to isolate the natural products responsible of these activities. Our investigation led to the isolation of three phytochemical constituents by the liquid chromatography method, the compounds were identified by spectroscopic analysis as flavonoids. The isolated compounds were identified as Quercetin 1, kaempferol-3-o-Î²-d-glucopyranoside (astragalin) 2 and quercetin-7-o-Î²-d-glucopyranoside 3. The presence of different types of bioactive constituents in the L. feei extract may explain it wide use by the local population. Keywords: Limoniastrum feei, Bioactive extract, Phytochemical screening, Flavonoid.